2013
DOI: 10.1063/1.4810931
|View full text |Cite
|
Sign up to set email alerts
|

A bi-functional structure with tunable electrical and optical properties for organic photovoltaic cells

Abstract: We have successfully developed a C60:LiF/BCP (bathocuproine) bilayer-buffer structure to optimize both the light absorption enhancement and the exciton-blocking at the cathode interface of a small molecular photovoltaic cell based on the archetypical CuPc/C60 structure. The function of the C60:LiF layer is to serve as an optical spacer and is found to yield a peak power conversion efficiency (PCE) with a 50 wt. % LiF at a thickness of 30 nm. A BCP layer is added between the optimized C60:LiF layer and the Al m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…4 However, other interpretations were also proposed to explain the role of BCP, such as increasing the built-in field, acting as an optical spacer, reducing nonradiative recombination of excitons at the fullerene (C 60 )/Al interface, avoiding the formation of aluminum carbide, and so on. 12,13 Anyway, the working mechanism is still controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, other interpretations were also proposed to explain the role of BCP, such as increasing the built-in field, acting as an optical spacer, reducing nonradiative recombination of excitons at the fullerene (C 60 )/Al interface, avoiding the formation of aluminum carbide, and so on. 12,13 Anyway, the working mechanism is still controversial.…”
mentioning
confidence: 99%
“…However, we found the electronic properties of BCP/metal interface are strongly dependent on the metal's WF by forming different dipole layers. 13 Moreover, it has been demonstrated that the energy level alignment of C 60 /BCP/Ag interfaces can be drastically influenced by BCP layer thickness. 12 This suggests that the increase of electric built-in field is not the only reason for the efficiency enhancement for OSC with BCP and low WF cathode, and other reasons should be considered.…”
mentioning
confidence: 99%
“…The cost of manufacturing optoelectronic devices is thus reduced rapidly [6,22], particularly when integrable light detection systems are taken into account [1,23], making them a viable alternative technology advantages over more classical designs such as silicon-based pressure sensors. Optoelectronic sensors have other advantages [24], such as negating the need for vacuum cavities to maintain high Q-factors needed for resonant devices [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Their most significant drawbacksshort lifetime and efficiency [1][2][3][4]-have been improved dramatically due to the intense research activity in this area in recent years. Being an innate surface-emitting light source, OLEDs are showing great commercial potential in the lighting industry, in mobile devices, and even in OLED televisions.…”
Section: Introductionmentioning
confidence: 99%
“…The designed monochromatic tandem OLEDs show lower working voltage and better efficiency than those of the single-luminescent-unit OLED without exciplex-forming architecture. [4][5][6][7] Herein, we go a significant step further to fabricate a novel highly simplified efficient tandem WOLED structure using energy transfer from exciplexes to complementary color doping-free UEMLs ((acetylacetonato)bis[2-(thieno[3,2-c]pyridin-4yl)phenyl]iridium(III) (PO-01) as yellow emitter and iridium(III) bis[(4,6-difluorophenyl)-pyridinato-N,C2′]-picolinate (FIrpic) as blue emitter). Particularly, the designed current-driven WOLEDs obtaining a peak of 40.53 cd/A (EQE=18.15%).…”
Section: Introductionmentioning
confidence: 99%